2020
DOI: 10.1007/s00394-020-02439-2
|View full text |Cite
|
Sign up to set email alerts
|

A mendelian randomization study on causal effects of 25(OH)vitamin D levels on attention deficit/hyperactivity disorder

Abstract: Background While observational studies revealed an inverse association between serum 25(OH)vitamin D (25(OH)D) and the risk of attention deficit/hyperactivity disorder (ADHD), the causality of this relationship remains unclear. Methods We conducted a bidirectional two-sample Mendelian Randomization (MR) study to examine whether 25(OH)D has an effect on the risk to develop ADHD or vice versa. Information on single nucleotide polymorphisms (SNP) associated with serum 25(OH)D was obtained from a genome-wide asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 44 publications
(76 reference statements)
0
6
0
2
Order By: Relevance
“…OCD and ADHD, the most common comorbidities in CTD, have also been linked to lower levels of vitamin D [ 6 , 21 ]. However, the result has been inconsistent [ 26 , 43 ] and the salience of these observations remains to be understood.…”
Section: Introductionmentioning
confidence: 99%
“…OCD and ADHD, the most common comorbidities in CTD, have also been linked to lower levels of vitamin D [ 6 , 21 ]. However, the result has been inconsistent [ 26 , 43 ] and the salience of these observations remains to be understood.…”
Section: Introductionmentioning
confidence: 99%
“…The participants, the physician who prescribed the medications, and the nutritionist were blinded to the allocated treatment. According to previous studies, 2000 IU of vitamin D is an optimum dosage for preventing diseases in children and adults without any side effects [ 43 , 44 ]. The intervention group received two tablets of vitamin D3 (1000 IU vitamin D3 per each tablet) daily for 3 months.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have reported that the severity of TD is highest between 10 and 12 years of age and that symptoms of TD can be improved by vitamin D supplementation ( 1 , 11 ). Contrastingly, some studies report no relation between vitamin D deficiency and severity of TD ( 12 , 13 ). To verify the correlation between vitamin D levels and TD severity, we evaluated this association in children with TD and in healthy controls in Shanghai, China.…”
Section: Introductionmentioning
confidence: 91%